Barriers to cancer rehabilitation: healthcare professionals’ perspective in Saudi Arabia - AlJohi, Amani A.; AlKathiri, Fatimah M.; Ajaj, Kawthar F.; Buragadda, Syamala; Madi, Sanaa M. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Background Cancer has a major impact on societies across the world and there is a significant rise in the global cancer burden. Due to advancements in cancer diagnosis and treatment, the number of cancer survivors is increasing. However, they face physical and cognitive challenges, which may affect their quality of life. The study aims to identify current clinical practice patterns and barriers to cancer rehabilitation from the perspective of Saudi healthcare professionals.Method All healthcare professionals providing care for cancer patients at King Fahad Medical City were invited to participate. Two semi-structured focus groups and 9 interviews were conducted. Participants were physicians and allied health professionals. The researcher led the discussions and recorded comments, facial expressions, and other non-verbal communication nuances. Content analysis was performed to identify and summarize themes.Results Four key themes related to barriers in cancer rehabilitation are identified: healthcare providers’ competencies and knowledge, communication barriers, limited rehabilitation services for cancer patients, and patient- and family-related barriers.Conclusion The study identifies current clinical practice patterns and various barriers to cancer rehabilitation from Saudi health care professionals’ perspective. The findings may help policy makers and stake holders to design effective rehabilitation guidelines for cancer rehabilitation.
Keywords: Cancer; Rehabilitation; Barriers; Healthcare providers